IMPLEMENTASI TEORI PERILAKU TERENCANA TERHADAP MINAT INVESTASI PADA GENERASI Z DI PASAR MODAL (STUDI PADA MAHASISWA PRODI ILMU ADMINISTRASI BISNIS UNIVERSITAS LAMPUNG) - Herry Kurniawan; Suripto suripto; M. Iqbal Harori (Jurnal Kompetitif Bisnis, 2023)
This study aims to determine how much influence attitudes, subjective norms, and behavioral control have on the investment interest of students of Business Administration Study Program, University of Lampung. The independent variables used in this study are Attitudes (X1), Subjective Norms (X2), Behavioral Control (X3), and Investment Interest as the dependent variable. This type of research is associative with a quantitative approach. The population in this study were active students of the UNILA Business Administration Study Program starting from the 2018-2022 class. The data was obtained from a questionnaire using a Likert scale which was distributed via Google from social media, namely WhatsApp. The sample in this study amounted to 122 respondents who were taken using a purposive sampling technique. Data in this study were analyzed using multiple linear regression analysis with SPSS 29.0 tools. The results of this study indicate that the attitude variable partially has no significant effect on the investment interest variable, the subjective norm variable partially has no significant effect on the investment interest variable, the perceived behavior control variable partially has a significant effect on the investment interest variable. However, the three independent variables in this study were tested simultaneously without having a significant effect simultaneously between attitude variables, subjective norms, and perceived behavioral control with interest variables.Keywords : Theory Planned Behavior, Attitude, Subjective Norm, Behavior control, Investment Interest